ENVIRONMENTAL MANAGEMENT ACCOUNTING. A CASE STUDY FOCUSING ON A ROMANIAN MOROCCO GOODS PRODUCER - JINGA, Gabriel; DUMITRU, Mădălina; RADU, Gabriel; STOIAN, Flavia (Annales Universitatis Apulensis Series Oeconomica, 2014)
In this article our focus is to develop a case study concerning the environmental management accounting (EMA) applied in a Romanian company which is acting as a morocco goods (shoes, bags, belts, wallets and other leather accessories) producer. We use as a research methodology the case study due to the fact that it is most desriptive in  assesing the specific settings that are of interest to the concerned users. We have selected this company because of its impact on the related environment. The study relies on the EMA framework designed by Burritt, Hahn and Schaltegger (2002). We have made a material life-cycle assessment for one type of product. Our study has multiple data sources (such as a large spectrum of related persons including production and financial managers, accountants, and company owners and CEO) as well as a variety of research methods (direct observation, documentation, archival records, and interviews). Our objective is to prove that EMA can help companies act in an integrated manner, improving their production process and their performance. By implementing EMA, managers can identify ways to improve the eco-efficiency of the companies.